Governance Deficits and Social Engineering Strategies in Community-Owned Enterprises: Evidence from Pulosari Village, Indonesia - Wardhana, Didin; Kushendar, Deden Hadi; Anggraeni, Heni; Sumardanu, Tri (Jurnal Manajemen Pelayanan Publik, 2026)
This study explores governance deficits within Community-Owned Enterprises (BUMW) and proposes social engineering strategies to enhance their sustainability. This qualitative case study employed interviews, observations, and document analysis involving key stakeholders of Pulosari Village-owned enterprise. The research focuses on five key governance pillars: institutional autonomy, citizen participation, transparency and accountability, local innovation, and digital integration. Social engineering strategies in this study refer to participatory and institutional governance interventions designed to strengthen organizational sustainability. The findings reveal persistent challenges, including limited legal recognition, participation that is more ceremonial than substantive, weak financial transparency, and minimal adoption of innovation and digital tools. These shortcomings undermine public trust, reduce community ownership, and threaten long-term viability. To address these issues, the study suggests several social engineering strategies, such as strengthening legal status, creating more inclusive decision-making forums, promoting participatory financial oversight, establishing local innovation incubators, and advancing community-based digitalization. Beyond contributing to public administration scholarship by situating BUMW within a governance framework, the study also offers practical recommendations for policymakers and community actors to improve accountability, inclusiveness, and sustainability.